Search for direct top squark pair production in final states with one isolated lepton, jets, and missing transverse momentum in sqrt[s] = 7 TeV pp collisions using 4.7 fb(-10 of ATLAS data. - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, O; Abramowicz, H; et al. (2012)
A search is presented for direct top squark pair production in final states with one isolated electron or muon, jets, and missing transverse momentum in proton-proton collisions at sqrt[s] = 7 TeV. The measurement is based on 4.7 fb(-1) of data collected with the ATLAS detector at the LHC. Each top squark is assumed to decay to a top quark and the lightest supersymmetric particle (LSP). The data are found to be consistent with standard model expectations. Top squark masses between 230 GeV and 440 GeV are excluded with 95% confidence for massless LSPs, and top squark masses around 400 GeV are excluded for LSP masses up to 125 GeV.